O que se estudou no Brasil sobre Alfabetização de 2016 a 2018 - Pereira Campos, Jessica Kamilla Mendes (2022)
Literacy, defined by many as the act of literacy, mainly linked to primary education to name reading and writing practices. But literacy goes far beyond knowing how to read and write. But it is not just restricted to primary education. This article aims to identify the characteristics of Brazilian scientific productions on literacy between 2016 and 2018. To respond to the proposed objective, the InOrdinatio Method proposed by Pagani et al. was used, considering the impact factor of the journal. It was concluded among the analyzed studies, half of the works extrapolated the study of literacy in primary education, with studies in the areas of health, adult education, financial literacy and teacher training. Among the studies that aimed to study literacy in primary education, most focused on reading and writing skills in primary education.